Development of an Anthropomorphic Shoulder Phantom Model That Simulates Bony Anatomy for Sonographic Measurement of the Acromiohumeral Distance. (1st November 2014) - Adusumilli, Pratik; McCreesh, Karen; Evans, Tony
Abstract : The purpose of this project was to create a sonographic phantom model of the shoulder that was accurate in bone configuration. Its main purpose was for operator training to measure the acromiohumeral distance. A computerized 3‐dimensional model of the superior half of the humerus and scapula was rendered and 3‐dimensionally printed. The bone model was embedded in a gelatin compound and set in a shoulder‐shaped mold. The materials used had speeds of sound that were well matched to soft tissue and epiphyseal bone. The model was specifically effective in simulating the acromiohumeral distance because of its accurate bone geometry.